2013
DOI: 10.1002/sim.5814
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian inference for multivariate meta‐analysis Box–Cox transformation models for individual patient data with applications to evaluation of cholesterol‐lowering drugs

Abstract: In this paper, we propose a class of Box-Cox transformation regression models with multidimensional random effects for analyzing multivariate responses for individual patient data (IPD) in meta-analysis. Our modeling formulation uses a multivariate normal response meta-analysis model with multivariate random effects, in which each response is allowed to have its own Box-Cox transformation. Prior distributions are specified for the Box-Cox transformation parameters as well as the regression coefficients in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 24 publications
0
30
0
Order By: Relevance
“…Other. Several one-stage models have been proposed for IPD-MA where the outcome belongs to another type of non-normally distributed data , recurrent events (Haines and Hill, 2011), repeated measurements , or multivariate responses (Kim et al, 2013;Riley et al, 2008;Yamaguchi et al, 2002).…”
Section: Countmentioning
confidence: 99%
“…Other. Several one-stage models have been proposed for IPD-MA where the outcome belongs to another type of non-normally distributed data , recurrent events (Haines and Hill, 2011), repeated measurements , or multivariate responses (Kim et al, 2013;Riley et al, 2008;Yamaguchi et al, 2002).…”
Section: Countmentioning
confidence: 99%
“…These L measures indicate that (i) the models with an unstructured Σ fit the cholesterol data much better than the respective models with a diagonal Σ; (ii) under an unstructured Σ, the t model fit the data better than the normal model; (iii) under both the diagonal Σ and unstructured Σ, the skew t models fit the data better than the symmetric normal and t models; (iv) under both the diagonal Σ and unstructured Σ, the skew t models with dependent z ijk ’s ( τ < ∞) outperformed the corresponding models with independent z ijk ’s ( τ = ∞ ); and (v) among the 9 models with a diagonal Σ, the skew t model with τ = 25 was the best while the skew t model with τ = 30 was the best among the 9 models with an unstructured Σ according to the L measure. These results are quite interesting and appealing since they showed that the three outcome variables were indeed dependent and the distributions of these variables were not symmetric for the cholesterol data as shown in Kim et al 1…”
Section: Analysis Of the Cholesterol Datamentioning
confidence: 70%
“…The proposed model includes multivariate normal meta-regression models, multivariate skew normal meta-regression models; and multivariate skew t meta-regression models as special cases. Compared to Kim et al 1 who used a Box-Cox transformation on the response variables, our proposed multivariate skew t meta-regression model is more attractive since the point estimates are more directly comparable and easier to interpret than those under a Box-Cox transformation model and the proposed model requires much less computational time. Estimation of the parameters requires a sophisticated and computationally intensive Markov chain Monte Carlo (MCMC) sampling algorithm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We first performed a Box-Cox Power Transformation [17] using a powerTransform function (car package in R 3.4.0) to make the distribution of each mRNA and lncRNA in each sample approximately normal.…”
Section: Methodsmentioning
confidence: 99%